2017
DOI: 10.1002/elps.201700098
|View full text |Cite
|
Sign up to set email alerts
|

CE and nanomaterials – Part II: Nanomaterials in CE

Abstract: The scope of this two-part review is to summarize publications dealing with CE and nanomaterials together. This topic can be viewed from two broad perspectives, and this article is trying to highlight these two approaches: (i) CE of nanomaterials, and (ii) nanomaterials in CE. The second part aims at summarization of publications dealing with application of nanomaterials for enhancement of CE performance either in terms of increasing the separation resolution or for improvement of the detection. To increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 213 publications
(203 reference statements)
0
8
0
Order By: Relevance
“…Nowadays, few analytical methods based on powerful separation techniques that introduced GQDs have been reported. In particular, since the use of nanomaterials in CE has proved to improve CE performance , Sun et al. reported the use of GQDs in the buffer solution as additive for improving the efficiency in separation of compounds of the same family .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, few analytical methods based on powerful separation techniques that introduced GQDs have been reported. In particular, since the use of nanomaterials in CE has proved to improve CE performance , Sun et al. reported the use of GQDs in the buffer solution as additive for improving the efficiency in separation of compounds of the same family .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, few analytical methods based on powerful separation techniques that introduced GQDs have been reported. In particular, since the use of nanomaterials in CE has proved to improve CE performance [7], Sun et al reported the use of GQDs in the buffer solution as additive for improving the efficiency in separation of compounds of the same family [8]. However, in CE the improvement of sensitivity is important, in order to be compared with other more expensive equipment like those chromatographic techniques combined with spectrometry detection.…”
Section: Introductionmentioning
confidence: 99%
“…NPs are a better choice for pseudo-SPs in background electrolytes. Using NPs as capillary wall coatings can effectively improve the Rs [ 71 ]. NPs in biological samples will form the outer layer on their surface, and this structure is called the “protein corona”.…”
Section: Advances In Chiral Separation Of Ot-cec Based On Sp Materialsmentioning
confidence: 99%
“…Note that, apart from QDs, noble metal nanomaterials, such as silver nanoclusters [36] and silver nanorod arrays [37], can also be employed in CE‐fluorescence analysis. General reviews of the studies can be found elsewhere [38, 39]. Moreover, because QDs exhibit strong absorption in the UV‐vis region, they were also employed in CE‐UV detection [40].…”
Section: Fluorescence Detectionmentioning
confidence: 99%